CFRP strengthened RC beams with pre-strengthening non-uniform reinforcement corrosion subjected to post-strengthening wetting/drying cycles. (15th November 2016) - Zhang, Dawei; Zhao, Yuxi; Ueda, Tamon; Li, Xiangmin; Xu, Qingfeng
Highlights: Investigate the effect of non-uniform corrosion on the yielding strength beams. Clarify the effect of pre-strengthening damage on the post-strengthening resistance. Propose analytical models considering the pre- or post-strengthening damage. Abstract: In practice, reinforced concrete (RC) structures before and after strengthening usually is exposed to a wide variety of combined actions, which may cause various damage to the structures. The main objectives of this study are to investigate the effects of three types of pre- and post- strengthening damage in the marine environment on the flexural behaviors of carbon fiber-reinforced polymer (CFRP)-strengthened RC beams and to develop a design methodology for predicting their yielding load, debonding load and peak load with or without CFRP debonding. The pre-damage was induced by either sustained load only or by the combination of sustained load and corrosion. The post-damage was induced by combined sustained load and wetting/drying (WD) cycles. The failure mode, yielding load, debonding load and peak load were recorded and compared, and the related mechanism was discussed. Subsequently, by adopting nonlinear sectional analysis, the effect of non-uniform corrosion of steel reinforcement on the yielding load, the effect of WD cycles on the debonding load and the effective CFRP rupture strain were examined and several models were proposed accordingly. The yielding strength, debonding strength and peak strength of the beams can be predicted by the proposed models with sufficient accuracy. The reliability of the proposed models was further validated with a collected database from the existing literatures.